2021
DOI: 10.1017/s1047951121000172
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, cellular, and molecular characterisation of cardiac rhabdomyoma in tuberous sclerosis

Abstract: Background: Rhabdomyoma is the most common cardiac tumour in children. It is usually associated with tuberous sclerosis complex caused by mutations in TSC-1 or TSC-2 genes. This tumour typically regresses by unknown mechanisms; however, it may cause inflow or outflow obstruction that necessitates urgent surgery. Here we investigate the clinical features and the genetic analysis of patients with tuberous sclerosis complex presenting with large rhabdomyoma tumours. We also investigate the potential role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 24 publications
(30 reference statements)
0
10
0
3
Order By: Relevance
“…The immunohistochemistry of this “first” tumor was also positive for SP-100 and negative for vimentin, which should have steered the clinician away from the diagnosis of rhabdomyoma ( 4 ). Spider cells are considered a pathognomonic finding of rhabdomyomas ( 7 ); this case demonstrates that pathognomonic findings rarely exist. The patient had a 2-year disease-free period, and a subsequent recurrence was documented with metastases to the diaphragm, liver, and regional ganglia.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The immunohistochemistry of this “first” tumor was also positive for SP-100 and negative for vimentin, which should have steered the clinician away from the diagnosis of rhabdomyoma ( 4 ). Spider cells are considered a pathognomonic finding of rhabdomyomas ( 7 ); this case demonstrates that pathognomonic findings rarely exist. The patient had a 2-year disease-free period, and a subsequent recurrence was documented with metastases to the diaphragm, liver, and regional ganglia.…”
Section: Discussionmentioning
confidence: 86%
“…PEComas are a group of tumors with a variety of histopathological presentations. Four main groups are described: angiomyolipoma, clear cell “sugar” tumor of the lung, lymphangioleiomyomatosis, and other tumors with similar features that are simply termed PEComa ( 7 ). Some PEComas are associated with tuberous sclerosis complexes.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac rhabdomyoma are benign tumors dependent of cardiac muscle fibers, being multiple, with a location of 70% in the left ventricle, with a tendency to decrease in size with spontaneous regression in 90% of cases, an association with tuberous sclerosis is described in 61-72%, sometimes causing mechanical obstruction, appearing during fetal age between 20 to 30 weeks of gestation, presenting regression in childhood in some cases, Kotulska et al found expressions of pro-apoptotic proteins in this type of tumors associated with tuberous sclerosis, fibromas were also found in 15.4% and myxomas in 5.8%, associated with tuberous sclerosis complex. [52][53][54][55][56][57] The clinical impact varies depending on the location and number of lesions, however, in most cases they are asymptomatic. On the other hand, when they develop symptoms, they vary from cardiomegaly, murmurs, arrhythmias, hydrops fetalis and depending on the location, they can generate an obstruction gradient that can even result in the death of the patient.…”
Section: Cardiac Manifestationsmentioning
confidence: 99%
“…Al Kindi et al found a high expression of autophagic proteins such as P62 and LC3b an apoptotic protein such as caspase 3 and 7 that are involved in the process of spontaneous regression of the lesion. 53,56,57 On echocardiography lesions are found in the wall of the right or left ventricle, in the left ventricular outflow tract, being mural lesions, pedunculated, multiple, of variables size, and hyperechoic (Figure 3). Other studies can be used, such as cardiac tomography, finding hypodense lesions after contrast and in cardiac magnetic resonance, isointense or hyperintense lesions in the myocardium at T2.…”
Section: Cardiac Manifestationsmentioning
confidence: 99%
“…In 2015, Muhammad described a large Bedouin family with severe recessive LVNC and found that autophagy flux was impaired in LVNC (12). In 2021, Al Kindi demonstrated the potential role of autophagy as a mechanism for genesis and regression of cardiac rhabdomyoma in TSC (13). Herein, we assumed a genetic association between the two disease processes.…”
mentioning
confidence: 96%